Consumer perceptions of cross-border e-commerce in the EU Digital Single Market - Melisande Cardona; Néstor Duch-Brown; Bertin Martens (European Commission, Joint Research Centre (JRC), 2015)
This report presents empirical evidence about the obstacles that European consumers face when trying to buy online goods and services in other EU Member States. It relies on data from a consumer survey carried out in February-March 2015 in the EU28. By comparing named websites with respondents' answers on the location of web shops, we find that 77% correctly assess whether a website is located domestically or in a foreign country. We also find that survey results are biased because cross-border purchases are under-reported. In addition, the report finds that prices, variety and transaction costs are strong drivers to shift consumer purchases of goods from offline to online shops, as predicted by economic theory. Consumers' perceptions of risk still hold them back from online transactions, which leaves some margin for policy makers to improve the regulatory and institutional setting. The results are less conclusive for online access to digital media content and for shifting online purchases from domestic to foreign markets.
Keywords: D12; 330